BEYOND EXPECTATIONS: IMAGINING DIGITAL SCHOLARSHIP IN THE HUMANITIES - Antonijevic, Smiljana (AoIR Selected Papers of Internet Research, 2015)
This paper examines the imaginaries within and about digital humanities (DH) as a scholarly field and as an area of practice. The paper draws on an ethnographic study conducted from 2010-2013. Through case studies, surveys, interviews, and observations the study explored humanists’ engagement with digital tools and resources, analyzed teams developing digital tools, and examined digital resource use within university departments. The fieldwork was carried out at twenty-three educational, research and funding institutions in the US and Europe, and it involved 258 participants including researchers, faculty, students, administrators, librarians, software developers, policy makers, and funders.